Family day care : international perspectives on policy, practice and quality - Mooney, Ann, 1950-; Statham, June (Jessica Kingsley Publishers, 2003)
Family day care or childminding plays a significant role in the provision of childcare in many countries, but is facing new challenges. Bringing together theory, research and knowledge from practice, this topical book presents a variety of informative perspectives on this important service. Contributors from ten countries draw on their recent research to examine how family day care has developed in differing economic and social climates. Covering the views of policy makers, childcare providers and parents, the book includes discussion of: levels of government intervention; training and support.